EFL LEARNERS' PERCEPTIONS OF BUSUU APPLICATION IN LANGUAGE LEARNING BY EVALUATING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) AT SMAN 9 WAJO - Amelia, Jamila; Rum, Eka Prabawati; Ariana (Journal of Computer Interaction in Education, 2024)
The aim of this research is to determine students' perceptions regarding the use of the Busuu application in learning English for class XI students at SMAN 9 Wajo. Researcher used quantitative descriptive research. The sample for this research was class XI students at SMAN 9 Wajo, totaling 20 students. Samples were taken using a questionnaire. Based on the findings, it was found that students gave positive perceptions about the use of Busuu in learning English, positive responses came from their experiences in the learning process. The research results showed that based on Likerts score analysis there were 19 (100%) students in the positive perception category with a score classification of 60-100, and no students had a negative perception. It is categorized that Busuu used in English language learning is effective to apply, helps the learning process in the classroom. Recommendations for further research are to conduct research related to the use of Busuu in teaching and learning processes such as Cake, Duolingo, along with technological advances that continue to increase from time to time.